2008
DOI: 10.1186/1471-2296-9-37
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the 'Designated Research Team' approach to building research capacity in primary care

Abstract: Background: This paper describes an evaluation of an initiative to increase the research capability of clinical groups in primary and community care settings in a region of the United Kingdom. The 'designated research team' (DRT) approach was evaluated using indicators derived from a framework of six principles for research capacity building (RCB) which include: building skills and confidence, relevance to practice, dissemination, linkages and collaborations, sustainability and infrastructure development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
99
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(105 citation statements)
references
References 11 publications
6
99
0
Order By: Relevance
“…[15] Support for mentorship and targeted team-based education for building research capacity has been reported in other studies. [11,16] In our study, the finding around the key role of the unit manager supporting their local research team is consistent with other work that identified managers to positively influence the unit culture and actively support research engagement. [4] Participating teams described the value of having an interprofessional collaborative team to work on the research project adding to the evolving literature base on the value of CPBR.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…[15] Support for mentorship and targeted team-based education for building research capacity has been reported in other studies. [11,16] In our study, the finding around the key role of the unit manager supporting their local research team is consistent with other work that identified managers to positively influence the unit culture and actively support research engagement. [4] Participating teams described the value of having an interprofessional collaborative team to work on the research project adding to the evolving literature base on the value of CPBR.…”
Section: Discussionsupporting
confidence: 75%
“…A team-based approach to build research capacity was reported to be effective in developing linkages and collaborations with participating members in primary care. [16] The challenges experienced by study participants were consistent with the literature including not have sufficient protected time [6,14,[20][21][22] or resources (e.g. budget, research staff).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Disciplines within primary and community health, such as general practice, nursing, midwifery and allied health, have a low research skills base and may lack the research infrastructure needed to develop knowledge for evidence-based practice (Ilott 2004;Cooke et al 2008). Several strategies to build research capacity in these disciplines have been reported in the UK , the USA (Frontera et al 2006) and Australia (Askew et al 2008;McIntyre et al 2011).…”
Section: Introductionmentioning
confidence: 99%